Differential Research and Analysis of Online Instruction Satisfaction of Instructors in Different Majors - Pengying Du, Hui Chen, Yunlei Sun, Hao Jiang, Guohong Chen (Forest Chemicals Review, 2022)
Under the special background of the coronavirus epidemic, online instruction is in full swing all over the world. The academic structure, system construction, and thinking habits of different majors are different. The satisfaction of online instruction of different majors was studied, It is of great significance to improve the quality of online instruction. A questionnaire survey was launched on 8203 instructors from 105 colleges and universities in China. The six different majors of humanities, social sciences, natural sciences, technical sciences, medical sciences, and art design were divided into 18 influencing factors as the independent variable. Satisfaction was used as the dependent variable. The reliability and validity were tested and the statistical validity was good. The principal component dimensionality reduction analysis was carried out by using the multiple linear regression analysis method. And three main factors of users, inductors and external environment were considered. The analysis results show that overall satisfaction of each specialty ranks as humanities>natural sciences> social sciences> technical sciences> art design> medical sciences. In order to promote the quality of talent training, several suggestions are given through analysis. The managers need to further improve the management service level, and the instructors need to increase investment, adopt diversified guidance modes and increase interaction.